Supported nickel-based catalyst, preparation method and application thereof, and method for producing hydrogen through ammonia decomposition
By using a catalyst with a nickel element supported by barium titanate, the problem of insufficient activity and stability of existing ammonia decomposition catalysts at low temperatures is solved, and efficient ammonia decomposition conversion at low temperatures and large space speeds is achieved, and the cost is low.
Patent Information
- Application Number
- CN202311410671.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-10-27
AI Technical Summary
The activity and stability of existing ammonia decomposition catalysts at low temperatures need to be further improved, especially at large space speeds, the ammonia decomposition conversion rate is relatively low.
Barium titanate is used as a support and nickel element is supported to prepare a supported nickel-based catalyst through impregnation method, which regulates the acid-base and electron transfer ability of the catalyst surface, and improves the interaction between the nickel active component and the support.
The ammonia decomposition activity and stability of the catalyst are significantly improved at low temperatures, and can maintain a high ammonia decomposition conversion rate at a large space speed, and does not contain precious metals and is cheap.
Smart Images

Figure BDA0004518074960000121 
Figure BDA0004518074960000131 
Figure BDA0004518074960000132
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of ammonia decomposition catalysts, and in particular to a supported nickel-based catalyst, a preparation method and application thereof, and a method for producing hydrogen by decomposing ammonia. Background Art
[0002] At present, hydrogen almost comes from the catalytic steam reforming of fossil fuels, which is also the most mature commercial hydrogen production technology. However, the hydrogen extracted by catalytic reforming will be accompanied by impurity gases such as carbon monoxide and carbon dioxide, and cannot be directly used as fuel cell fuel. Therefore, using hydrogen-rich carrier ammonia as a raw material for carbon-free hydrogen production is an efficient, clean and safe hydrogen production technology. In order to achieve safe and green hydrogen production, it is particularly important to develop catalysts that can efficiently catalyze the decomposition of ammonia. At present, ammonia decomposition catalysts are divided into precious metal catalysts with ruthenium and platinum as active components and non-precious metal catalysts with iron and nickel as active components.
[0003] The high cost and low reserves of precious metals limit their application in large-scale industrialization. Therefore, the core of developing efficient and low-cost ammonia decomposition hydrogen production technology lies in low-cost, high-activity and high-stability non-precious metal catalysts. However, non-precious metal catalysts require more stringent reaction conditions, and the operating temperature is generally higher than 800°C. For this reason, extensive research has been conducted on low-temperature non-precious metal ammonia decomposition catalysts. For example, CN1506299A discloses a nickel-based ammonia decomposition hydrogen-nitrogen mixed gas catalyst, whose main active component is Ni; the carrier is SiO 2 or Al 2 O 3 The auxiliary agent is one or more of IA, IIA, IIIB, VIII or rare earth elements; the weight percentage of nickel is 1-40%; the weight percentage of auxiliary agent components is 0.1-20%. 2 or Al 2 O 3 As a carrier for preparing catalysts, although the introduction of additives improves its performance, ammonia decomposition can be carried out at 650°C, which is significantly lower than the reaction temperature of 800°C for industrial catalysts. However, due to the poor dispersion of the additives on the carrier surface, large particles are easily formed, resulting in poor ammonia decomposition activity at low temperatures. CN115646500A discloses a catalyst for hydrogen production by decomposing ammonia, which includes an active metal component, an alkaline earth metal component, a lanthanide metal component and an additive. The patent application uses alkaline earth metal doping to improve the dispersion of the nickel-based catalyst and reduce the particle size. Compared with the unmodified catalyst, the activity of the catalyst in this patent has been improved to a certain extent. Although the reaction temperature is reduced to 550°C, the reaction space velocity is only 6000mL / (g·h), and there is still room for improvement. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem that the activity and stability of the existing ammonia decomposition catalyst at low temperature need to be further improved, and to provide a supported nickel-based catalyst and its preparation method and application, as well as a method for producing hydrogen by decomposing ammonia. The catalyst has high activity, is applied to the production of hydrogen by decomposing ammonia, and has a high ammonia decomposition conversion rate at low temperature and high space velocity.
[0005] In order to achieve the above object, the present invention provides a supported nickel-based catalyst, which contains a barium titanate carrier and a nickel element supported on the barium titanate carrier, wherein the nickel content is 2-15% by weight based on the total weight of the catalyst and calculated as nickel oxide;
[0006] Wherein, the average particle size of the catalyst is 1-10 microns.
[0007] A second aspect of the present invention provides a method for preparing a supported nickel-based catalyst, the method comprising the following steps:
[0008] S1, grinding the titanium-containing compound and the barium-containing compound to obtain a powder with an average particle size of 0.1-7 microns;
[0009] S2, drying and first calcining the powder obtained in S1 to obtain a barium titanate carrier;
[0010] S3. The nickel element is loaded on the barium titanate carrier by an impregnation method.
[0011] The third aspect of the present invention provides an application of the supported nickel-based catalyst described in the first aspect or the supported nickel-based catalyst prepared by the preparation method described in the second aspect in hydrogen production by decomposing ammonia.
[0012] A fourth aspect of the present invention provides a method for producing hydrogen by decomposing ammonia, the method comprising: contacting ammonia with a catalyst under conditions of ammonia decomposition;
[0013] Wherein, the catalyst is the catalyst described in the first aspect or the supported nickel-based catalyst prepared by the preparation method described in the second aspect.
[0014] Through the above technical solution, the beneficial effects of the present invention include:
[0015] The catalyst provided by the present invention uses barium titanate and nickel active components to work synergistically, so that the activity of the catalyst at low temperatures is improved; at the same time, the content of nickel element is in the range of 2-15 weight%, which is conducive to enhancing the interaction between the nickel active component and the carrier, and effectively weakening the interaction between the active component and the ammonia decomposition product, thereby promoting the desorption of nitrogen and hydrogen. Preferably, the catalyst of the present invention does not contain precious metals such as Ru, and has low cost.
[0016] The preparation process of the supported nickel-based catalyst of the present invention is simple, has good repeatability and is easy to carry out large-scale production. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] The first aspect of the present invention provides a supported nickel-based catalyst, the catalyst comprising a barium titanate carrier and a nickel element supported on the barium titanate carrier; based on the total weight of the catalyst, the nickel content is 2-15% by weight in terms of nickel oxide;
[0019] Wherein, the average particle size of the catalyst is 1-10 microns.
[0020] The inventors of the present invention have found that using barium titanate as a carrier can effectively regulate the acidity and alkalinity of the catalyst surface, regulate the electron transfer capacity between the active components in the catalyst and the carrier, and regulate NH 3 The adsorption and desorption strength on the catalyst surface promotes NH 3 Transfer between active sites and supports to improve catalytic activity.
[0021] In the present invention, based on the total weight of the catalyst, the nickel content is 2-15% by weight, preferably 5-15% by weight, such as 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, and any value in the range formed by any two of these values. This preferred embodiment is conducive to enhancing the interaction between the nickel active component and the carrier, and effectively weakening the interaction between the active component and the ammonia decomposition product, thereby promoting the desorption of nitrogen and hydrogen.
[0022] The total content of each component of the catalyst of the present invention is 100%.
[0023] The content of active components in the catalyst of the present invention is measured by XRF characterization method.
[0024] According to the present invention, preferably, the average particle size of the catalyst is 1-10 microns, preferably 2-8 microns, for example, 1 micron, 2 microns, 3 microns, 4 microns, 5 microns, 6 microns, 7 microns, 8 microns, 9 microns, 10 microns, and any value in the range formed by any two of these values. This preferred embodiment is conducive to promoting the uniform distribution of active components on the catalyst surface, thereby improving the activity of the catalyst.
[0025] The average particle size of the catalyst of the present invention is measured by a particle size analyzer.
[0026] Preferably, the catalyst does not contain precious metals. This preferred embodiment can save costs.
[0027] A second aspect of the present invention provides a method for preparing a catalyst, the method comprising the following steps:
[0028] S1, grinding the titanium-containing compound and the barium-containing compound to obtain a powder with an average particle size of 0.1-7 microns;
[0029] S2, drying and first calcining the powder obtained in S1 to obtain a barium titanate carrier;
[0030] S3. The nickel element is loaded on the barium titanate carrier by an impregnation method.
[0031] The preparation method provided by the present invention first adopts a solid phase synthesis method to prepare a barium titanate carrier, and then adopts an impregnation method to load the nickel active component on the barium titanate carrier, so that a catalyst with high activity and good stability can be obtained by a simple method.
[0032] According to the present invention, preferably, in S1, the molar ratio of the barium-containing compound to the titanium-containing compound is 1:2-8, preferably 1:2-6.
[0033] The present invention has a wide range of selection for the type of the titanium-containing compound. Preferably, the titanium-containing compound is titanium dioxide and / or metatitanic acid.
[0034] The present invention has a wide range of selection for the type of the barium-containing compound. Preferably, the barium-containing compound is barium carbonate and / or barium hydroxide.
[0035] According to the present invention, preferably, the average particle size of the powder obtained in S1 is 1-6 microns, for example, 1 micron, 2 microns, 3 microns, 4 microns, 5 microns, 6 microns, and any value in the range formed by any two of these values. This preferred embodiment is conducive to obtaining the catalyst with the average particle size described in the first aspect.
[0036] The present invention has no particular limitation on the grinding conditions in S1, as long as the powder having the above average particle size is obtained. Preferably, the grinding conditions in S1 include: a rotation speed of 150-600 rpm, preferably 200-400 rpm; and a grinding time of 3-60 min, preferably 5-30 min.
[0037] The present invention has no particular limitation on the apparatus for grinding, and various apparatuses conventionally used in grinding in the art can be used. A ball mill is preferably used in the present invention.
[0038] The present invention has no particular limitation on the specific conditions of the drying, and the drying can be carried out according to conventional methods in the art. Preferably, in S2, the drying conditions include: a temperature of 70-120°C and a time of 8-48 hours.
[0039] According to the present invention, preferably, in S2, the first calcination conditions include: a temperature of 600-900° C. and a time of 2-6 hours. This preferred embodiment is helpful to promote the subsequent interaction between the active component and the carrier.
[0040] According to the present invention, preferably, the impregnation method in S3 comprises:
[0041] (1) adding an aqueous solution containing a nickel salt to a barium titanate carrier to obtain a catalyst precursor;
[0042] (2) The catalyst precursor is aged, dried and calcined for a second time.
[0043] The use of this preferred embodiment is beneficial to the diffusion and secondary crystallization of nickel ions on the surface of the barium titanate carrier, and further beneficial to the improvement of the catalyst activity.
[0044] Preferably, step (1) comprises: adding an aqueous solution containing a nickel salt to a barium titanate carrier in a dropwise manner to obtain a catalyst precursor.
[0045] According to a specific embodiment of the present invention, an aqueous solution containing nickel salt is added dropwise onto a barium titanate carrier while stirring to obtain a catalyst precursor.
[0046] The present invention has no particular limitation on the stirring rate, which can be appropriately selected according to specific circumstances to ensure uniform mixing.
[0047] According to the present invention, preferably, the nickel salt is used in an amount such that the nickel content in the prepared catalyst is 2-15 wt %, preferably 5-15 wt %, calculated as nickel oxide, based on the total weight of the catalyst.
[0048] The present invention has no particular limitation on the type of the nickel salt, which can be selected conventionally in the art. Preferably, the nickel salt is nickel nitrate and / or nickel hydrochloride.
[0049] Preferably, the concentration of the nickel salt aqueous solution is 0.3-1.5 mol / L.
[0050] According to the present invention, preferably, the aging conditions in step (2) include: a temperature of 40-60° C. and a time of 1-3 hours.
[0051] The present invention has no particular limitation on the drying in step (2), which can be carried out according to conventional methods in the art, and will not be described in detail herein.
[0052] According to the present invention, preferably, the conditions of the second calcination in step (2) include: a temperature of 550-780° C. and a time of 2-5 hours. This preferred embodiment is conducive to uniform distribution of nickel oxide and to improving the catalytic performance of the catalyst.
[0053] According to the present invention, preferably, the method further comprises: reducing the product of the second calcination to obtain the catalyst.
[0054] The present invention has no particular limitation on the reduction conditions, and the reduction can be carried out according to conventional methods in the art. Preferably, the reduction conditions include: a temperature of 600-800° C. and a time of 1-3 h.
[0055] According to the present invention, preferably, the reduction is carried out in a reducing gas, the reducing gas comprises hydrogen and optionally an inert gas; in the reducing gas, the volume content of hydrogen is 10-100%.
[0056] In the present invention, unless otherwise specified, the term "optionally" means containing or not containing, adding or not adding, adopting or not adopting. Specifically, an inert gas may or may not be added in the reduction step of the present invention.
[0057] According to the present invention, preferably, the inert gas is selected from at least one of nitrogen, helium, argon and neon.
[0058] In the present invention, the "first" and "second" do not limit the substances and operations, but are only used to distinguish the substances introduced in different steps and the operations performed in different stages.
[0059] The third aspect of the present invention provides an application of the supported nickel-based catalyst described in the first aspect or the supported nickel-based catalyst prepared by the preparation method described in the second aspect in hydrogen production by decomposing ammonia.
[0060] A fourth aspect of the present invention provides a method for producing hydrogen by decomposing ammonia, the method comprising: contacting ammonia with a catalyst under conditions of ammonia decomposition;
[0061] Wherein, the catalyst is the catalyst described in the first aspect or the supported nickel-based catalyst prepared by the preparation method described in the second aspect.
[0062] In the prior art, the temperature of the ammonia decomposition reaction using a catalyst without precious metals is generally higher than 550° C. However, the catalyst of the present invention still has a high ammonia decomposition activity at low temperatures, and the ammonia decomposition temperature can be as low as 550° C. Moreover, the ammonia decomposition reaction of the present invention can be carried out at a relatively high space velocity, and the ammonia decomposition activity is still maintained at a relatively high level after a long-term evaluation experiment, indicating that the catalyst of the present invention has good stability.
[0063] According to the present invention, preferably, the conditions for decomposing ammonia include: a temperature of 550-650° C. and a volume space velocity of 5000-20000 mL / (g·h).
[0064] The present invention will be described in detail below through examples.
[0065] In the following examples, the ammonia decomposition conversion rate formula is as follows:
[0066] Ammonia decomposition conversion rate = (raw material ammonia content - product ammonia content) / raw material ammonia content × 100%.
[0067] Example 1
[0068] 13.42 g of titanium dioxide and 16.58 g of barium carbonate were weighed and mixed into a ball mill and ground at 200 rpm for 15 min to obtain a powder with an average particle size of 6.9 μm. The powder was dried at 120° C. for 2 h and then calcined at 800° C. for 4 h to obtain a barium titanate carrier.
[0069] Weigh 1.74g nickel chloride and dissolve it in deionized water to prepare a 0.5mol / L nickel chloride solution, and drop the nickel chloride solution into 9g barium titanate powder drop by drop, stirring while dropping to obtain a catalyst precursor. The obtained catalyst precursor was aged at 50°C for 2h, then dried at 120°C for 9h, and calcined at 550°C for 2h to obtain a calcined product. The calcined product was reduced at 700°C for 3h with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% to obtain a supported nickel-based catalyst. The catalyst composition and characteristic parameters are shown in Table 1.
[0070] Example 2
[0071] 18.54 g of titanium dioxide and 11.46 g of barium carbonate were weighed and mixed into a ball mill and ground at 400 rpm for 20 min to obtain a powder with an average particle size of 5 μm. The powder was dried at 120° C. for 2 h and then calcined at 800° C. for 4 h to obtain a barium titanate carrier.
[0072] Weigh 1.74g nickel chloride and dissolve it in deionized water to prepare a 0.5mol / L nickel chloride solution, and drop the nickel chloride solution into 9g barium titanate powder drop by drop, stirring while dropping to obtain a catalyst precursor. The obtained catalyst precursor was aged at 50°C for 2h, then dried at 120°C for 9h, and calcined at 550°C for 2h to obtain a calcined product. The calcined product was reduced at 700°C for 3h with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 15% to obtain 10g of a supported nickel-based catalyst. The catalyst composition and characteristic parameters are shown in Table 1.
[0073] Example 3
[0074] Weigh 21.25g of titanium dioxide and 7.6g of barium hydroxide, mix and add into a ball mill, grind at 400rpm for 20min, and obtain a powder with an average particle size of 4.8 microns. Dry the powder at 120℃ for 2h, and calcine at 800℃ for 4h to obtain a barium titanate carrier.
[0075] Weigh 1.74g nickel chloride and dissolve it in deionized water to prepare a 0.5mol / L nickel chloride solution, and drop the nickel chloride solution into 9g barium titanate powder drop by drop, stirring while dropping to obtain a catalyst precursor. The obtained catalyst precursor was aged at 50°C for 2h, then dried at 120°C for 9h, and calcined at 600°C for 2h to obtain a calcined product. The calcined product was reduced at 700°C for 3h with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 15% to obtain 10g of a supported nickel-based catalyst. The catalyst composition and characteristic parameters are shown in Table 1.
[0076] Example 4
[0077] 18.54 g of titanium dioxide and 11.46 g of barium carbonate were weighed and mixed into a ball mill and ground at 400 rpm for 30 min to obtain a powder with an average particle size of 4.1 μm. The powder was dried at 100° C. for 2 h and then calcined at 800° C. for 4 h to obtain a barium titanate carrier.
[0078] Weigh 1.74g nickel chloride and dissolve it in deionized water to prepare a 0.5mol / L nickel chloride solution, and drop the nickel chloride solution into 9g barium titanate powder drop by drop, stirring while dropping to obtain a catalyst precursor. The obtained catalyst precursor was aged at 50°C for 2h, then dried at 120°C for 9h, and calcined at 550°C for 2h to obtain a calcined product. The calcined product was reduced at 700°C for 3h with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 15% to obtain 10g of a supported nickel-based catalyst. The catalyst composition and characteristic parameters are shown in Table 1.
[0079] Example 5
[0080] 18.54 g of titanium dioxide and 11.46 g of barium carbonate were weighed and mixed into a ball mill and ground at 400 rpm for 5 min to obtain a powder with an average particle size of 6.8 μm. The powder was dried at 120° C. for 2 h and then calcined at 800° C. for 4 h to obtain a barium titanate carrier.
[0081] Weigh 1.74g nickel chloride and dissolve it in deionized water to prepare a 0.5mol / L nickel chloride solution, and drop the nickel chloride solution drop by drop into 9g magnesium titanate powder while stirring to obtain a catalyst precursor. The obtained catalyst precursor was aged at 45°C for 3h, then dried at 120°C for 12h, and calcined at 550°C for 2h to obtain a calcined product. The calcined product was reduced at 700°C for 3h with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 15% to obtain 10g of a supported nickel-based catalyst. The catalyst composition and characteristic parameters are shown in Table 1.
[0082] Example 6
[0083] 18.54 g of titanium dioxide and 11.46 g of barium carbonate were weighed and mixed into a ball mill and ground at 400 rpm for 20 min to obtain a powder with an average particle size of 5 μm. The powder was dried at 120° C. for 2 h and then calcined at 700° C. for 5 h to obtain a barium titanate carrier.
[0084] Weigh 0.35g of nickel chloride and dissolve it in deionized water to prepare a 0.5mol / L nickel chloride solution. Add the nickel chloride solution drop by drop into 9.8g of barium titanate powder while stirring to obtain a catalyst precursor. The obtained catalyst precursor was aged at 50°C for 2h, then dried at 110°C for 9h, and calcined at 550°C for 2h to obtain a calcined product. The calcined product was reduced at 700°C for 3h with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 15% to obtain 10g of a supported nickel-based catalyst. The catalyst composition and characteristic parameters are shown in Table 1.
[0085] Example 7
[0086] 18.54 g of titanium dioxide and 11.46 g of barium carbonate were weighed and mixed into a ball mill and ground at 400 rpm for 20 min to obtain a powder with an average particle size of 5 μm. The powder was dried at 120° C. for 2 h and then calcined at 800° C. for 4 h to obtain a barium titanate carrier.
[0087] Weigh 2.6g of nickel chloride and dissolve it in deionized water to prepare a 0.5mol / L nickel chloride solution. Add the nickel chloride solution drop by drop into 8.5g of barium titanate powder while stirring to obtain a catalyst precursor. The obtained catalyst precursor was aged at 50°C for 2h, then dried at 120°C for 9h, and calcined at 550°C for 2h to obtain a calcined product. The calcined product was reduced at 750°C for 2h with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 15% to obtain 10g of a supported nickel-based catalyst. The catalyst composition and characteristic parameters are shown in Table 1.
[0088] Example 8
[0089] The method of Example 1 was followed, except that barium titanate was prepared by precipitation method: tetrabutyl titanate was used as the titanium source, 57.18 g of tetrabutyl titanate was dissolved in 200 ml of anhydrous ethanol, and the pH was adjusted to about 1.4 with hydrochloric acid to obtain a titanium source solution; 21.95 g of barium nitrate was dissolved in 100 mL of deionized water to obtain a barium source solution, the prepared titanium source solution was added dropwise to the barium source solution and reacted at 30° C. for 2 h, the generated white precipitate was washed and filtered, and then dried at 120° C. for 9 hours, and the dried solid was calcined at 700° C. for 4 h in a muffle furnace to obtain barium titanate solid.
[0090] Using 9 g of barium titanate, 10 g of catalyst was obtained.
[0091] Comparative Example 1
[0092] Weigh 2.6g of nickel chloride and dissolve it in deionized water to prepare a 0.5mol / L nickel chloride solution. Add the nickel chloride solution drop by drop into 8.5g of titanium dioxide powder while stirring to obtain a catalyst precursor. The obtained catalyst precursor was aged at 50°C for 2h, then dried at 120°C for 9h, and calcined at 550°C for 2h to obtain a calcined product. The calcined product was reduced at 700°C for 3h with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 15% to obtain 10g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.
[0093] Comparative Example 2
[0094] Weigh 1.74g nickel chloride and dissolve it in deionized water to prepare a 0.5mol / L nickel chloride solution, and add the nickel chloride solution drop by drop into 9g titanium dioxide powder while stirring to obtain a catalyst precursor. The obtained catalyst precursor was aged at 50°C for 2h, then dried at 120°C for 9h, and calcined at 550°C for 2h to obtain a calcined product. The calcined product was reduced at 700°C for 3h with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 15% to obtain 10g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.
[0095] Comparative Example 3
[0096] The method of Example 1 was followed, except that an equimolar amount of magnesium carbonate was added instead of barium carbonate to obtain 10 g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.
[0097] Comparative Example 4
[0098] The method of Example 1 was followed, except that 13.42 g of titanium dioxide and 16.58 g of barium carbonate were weighed and mixed into a ball mill, and ground at 50 rpm for 5 min to obtain a powder with an average particle size of 22.3 μm. 10 g of a supported nickel-based catalyst was obtained. The catalyst composition and characteristic parameters are shown in Table 1.
[0099] Comparative Example 5
[0100] The method of Example 1 was followed, except that the amount of nickel chloride was adjusted so that the prepared catalyst had a nickel content of 20% by weight based on the total weight of the catalyst and calculated as nickel oxide. The catalyst composition and characteristic parameters are shown in Table 1.
[0101] Table 1
[0102]
[0103]
[0104] Note: In the catalyst, the balance is barium titanate carrier.
[0105] Test Example 1
[0106] At different temperatures, the activity of the catalyst was evaluated using ammonia nitrogen gas with an ammonia concentration of 15% by volume. 1 g of the catalyst prepared in the embodiment and the comparative example with a size of 40-60 mesh and 4 g of quartz sand with a size of 40-60 mesh were mixed and loaded respectively. The volume space velocity was 15000 mL / (g·h). The results of the reaction for 6 h are shown in Table 2.
[0107] Table 2
[0108]
[0109] It can be seen from the results in Table 2 that, under the same reaction conditions, the application of the catalyst of the present invention in the ammonia decomposition hydrogen production reaction has a significantly higher ammonia decomposition conversion rate.
[0110] At the same time, compared with the comparative example, the catalyst provided by the embodiment of the present invention has a significantly higher ammonia decomposition conversion rate at 550° C., indicating that the catalyst of the present invention has a higher ammonia decomposition activity at low temperatures.
[0111] Compared with the comparative example, the catalyst provided by the embodiment of the present invention has a significantly higher ammonia decomposition conversion rate at a higher space velocity, indicating that the catalyst of the present invention has good stability.
[0112] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A supported nickel-based catalyst, characterized in that The catalyst contains a barium titanate carrier and a nickel element loaded on the barium titanate carrier; based on the total weight of the catalyst, the nickel content is 2-15% by weight in terms of nickel oxide; Wherein, the average particle size of the catalyst is 1-10 microns.
2. The catalyst according to claim 1, wherein The nickel content is 5-15% by weight, calculated as nickel oxide, based on the total weight of the catalyst; Preferably, the average particle size of the catalyst is 2-8 microns.
3. A method for preparing a supported nickel-based catalyst, the method comprising the following steps: S1, grinding the titanium-containing compound and the barium-containing compound to obtain a powder with an average particle size of 0.1-7 microns; S2, drying and first calcining the powder obtained in S1 to obtain a barium titanate carrier; S3. The nickel element is loaded on the barium titanate carrier by an impregnation method.
4. The method according to claim 3, wherein: In S1, the molar ratio of the barium-containing compound to the titanium-containing compound is 1:2-8, preferably 1:2-6; Preferably, the titanium-containing compound is titanium dioxide and / or metatitanic acid; Preferably, the barium-containing compound is barium carbonate and / or barium hydroxide; Preferably, the average particle size of the powder obtained in S1 is 1-6 microns; Preferably, the grinding conditions in S1 include: a rotation speed of 150-600 rpm, preferably 200-400 rpm; and a grinding time of 3-60 min, preferably 5-30 min.
5. The method according to claim 4, wherein: In S2, the drying conditions include: a temperature of 70-120° C. and a time of 8-48 hours; Preferably, in S2, the conditions of the first calcination include: a temperature of 600-900° C. and a time of 2-6 hours.
6. The method according to any one of claims 3 to 5, wherein: S3 The impregnation method comprises: (1) adding an aqueous solution containing a nickel salt to a barium titanate carrier to obtain a catalyst precursor; (2) The catalyst precursor is aged, dried and calcined for a second time.
7. The method according to claim 6, wherein: The nickel salt is used in an amount such that the nickel content in the prepared catalyst is 2-15% by weight, preferably 5-15% by weight, calculated as nickel oxide, based on the total weight of the catalyst; Preferably, the nickel salt is nickel nitrate and / or nickel hydrochloride; Preferably, the aging conditions in step (2) include: a temperature of 40-60° C. and a time of 1-3 hours; Preferably, the conditions for the second calcination in step (2) include: a temperature of 550-780° C. and a time of 2-5 hours.
8. The method according to claim 6, wherein: The method further comprises: reducing the product of the second calcination to obtain the catalyst; Preferably, the reduction conditions include: temperature of 600-800°C and time of 1-3h; Preferably, the reduction is carried out in a reducing gas, the reducing gas comprising hydrogen and optionally an inert gas; in the reducing gas, the volume content of hydrogen is 10-100%; Preferably, the inert gas is selected from at least one of nitrogen, helium, argon and neon.
9. Use of the catalyst according to claim 1 or 2 or the catalyst prepared by the preparation method according to any one of claims 3 to 8 in the production of hydrogen by decomposing ammonia.
10. A method for producing hydrogen by decomposing ammonia, the method comprising: contacting ammonia with a catalyst under conditions that decompose ammonia; Wherein, the catalyst is the catalyst according to claim 1 or 2 or the catalyst prepared by the preparation method according to any one of claims 3 to 8; Preferably, the conditions for decomposing ammonia include: a temperature of 550-650° C. and a volume space velocity of 5000-20000 mL / (g·h).
Citation Information
Patent Citations
Catalyst for hydrogen production through ammonia decomposition as well as preparation method and application of catalyst
CN115646500A
Prepn and application of nickel-based catalyst for decomposing ammonia to prepare mixed H2-N2 gas
CN1506299A
Supported type nickel catalyst for producing hydrogen from decomposition of ammonia and preparation method
CN101352685A
Nickel-based catalyst and preparation method thereof
CN103055868A
Method for preparing supported metal catalyst through solvent-free mechanical mixing
CN103736487A